PENERAPAN KELUARGA SADAR GIZI: HARAPAN MENUJU TARGET NASIONAL - Artika Nurrahima (Poltekkes Kemenkes Jakarta III, 2016)
Children under five as one of the populations at risk for experiencing nutritionalproblems, which is become a global health problem. The prevalence of childmalnutrition in the world and Indonesia is high. One effort to overcome theproblems with a program called keluarga sadar gizi (Kadarzi). This study aims todescribe the application of Kadarzi. The research design was a descriptive crosssectional approach. Sample of this study was 103 families with children under fivein accordance with the inclusion criteria taken by clustrer sampling tehnique. Theresults showed good application Kadarzi as much as 52.4% and as much as47.6% less. Implementation of regularly weigh as much as 61.2%, exclusivebreastfeeding as much as 52.4%, eating diversified food as much as 56.3%, theconsumption of iodized salt as much as 53.4%, and consumption of vitamin A asmuch as 51.5 %. Implementation of the five indicators Kadarzi was lower than theachievements of Kadarzi in Depok City and national targets. Required theassistance Kadarzi implementation and regular home visits by health personnelrelated.